Small intestinal bacterial overgrowth in obese patients with biopsy-confirmed metabolic dysfunction-associated steatotic liver disease: a cross-sectional study - Ortiz-López, Nicolás; Madrid, Ana María; Aleman, Larissa; Zazueta, Alejandra; Smok, Gladys; Valenzuela-Pérez, Lucía; Poniachik, Jaime; Beltrán, Caroll J. (Frontiers in Medicine, 2024)
Background/Aims: The metabolic dysfunction-associated steatostic liver disease (MASLD) and obesity are frequent comorbidities with a high prevalence worldwide. Their pathogenesis are multifactorial, including intestinal dysbiosis. The role of small intestinal bacterial overgrowth (SIBO) in MASLD progression in obese patients remains unknown. We aimed to determine the association between SIBO and the severity of MASLD in obese patients. Methods: An observational and cross-sectional study was conducted in obese patients, diagnosed with or without MASLD by liver biopsy. metabolic dysfunction-associated steatostic liver (MASL), metabolic dysfunction-associated steatohepatitis without fibrosis (MASH-NF), MASH with fibrosis (MASH-F), or without MASLD (control subjects, CS) were identified by presence of steatosis, portal and lobular inflammation, and fibrosis. SIBO was determined by standardized lactulose breath tests. Results: A total of 59 patients with MASLD, 16 with MASL, 20 with MASH-NF, 23 with MASH-F, and 14 CS were recruited. Higher percentages of SIBO were observed in MASLD patients (44.2%) compared to CS (14.2%) (p = 0.0363). Interestingly, MASH-F showed higher percentages of SIBO (65.2%) in comparison to non-fibrotic MASLD (33.3%) (p = 0.0165). The presence of SIBO was not correlated with the level of hepatic steatosis in MASLD patients. Conclusions: A positive correlation between MASLD and SIBO in obese patients was principally explained by the presence of liver fibrosis. Our findings suggest a pathogenic role of intestinal dysbiosis in the progression of MASLD. Future research will elucidate the underlying mechanisms of SIBO in MASLD advancement.